PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN PADA PRODUK SKINTIFIC (Studi Kasus Mahasiswa Universitas 17 Agustus 1945 Surabaya) - Fredyta Wijianti; Endah Budiarti (CV SWA Anugrah, 2024)
This research aims to determine the influence of product quality and price perception on consumer satisfaction with Skintific products. The data used is primary data from questionnaires distributed on Google Form with a total of 100 respondents. Data were analyzed using multiple linear regression techniques and coefficient of determination () using the SPSS 27 application. The results of the analysis showed that the Product Quality variable had a significant influence on Consumer Satisfaction with Skintific products, then the Price Perception variable had a significant influence on Consumer Satisfaction on Skintific products.